2016
DOI: 10.1093/neuonc/now238
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of response and relapse in primary CNS lymphomas after first-line chemotherapy: imaging analysis of the ANOCEF-GOELAMS prospective randomized trial

Abstract: Background. Our aim was to review MRI characteristics of patients with primary CNS lymphoma (PCNSL) enrolled in a randomized phase II trial and to evaluate their potential prognostic value and patterns of relapse, including T2 fluid attenuated inversion recovery (FLAIR) MRI abnormalities. Methods. Neuroimaging findings in 85 patients with PCNSL enrolled in a prospective trial were reviewed blinded to outcomes. MRI characteristics and responses according to International PCNSL Collaborative Group (IPCG) criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 25 publications
6
44
1
Order By: Relevance
“…9 This observation is consistent with the fact that lymphomatous dissemination in the brain may occur in the absence of contrast enhancement on MRI (Figure 2). …”
Section: Diagnosis Pathogenesis and Radiographic Assessmentsupporting
confidence: 89%
“…9 This observation is consistent with the fact that lymphomatous dissemination in the brain may occur in the absence of contrast enhancement on MRI (Figure 2). …”
Section: Diagnosis Pathogenesis and Radiographic Assessmentsupporting
confidence: 89%
“…This dynamic change indicated that these white matter non-enhancing T2-FLAIR hyperintensity lesions had neoplastic nature. It has been reported that the prevalence of this phenomenon was about 23% [13]. In our research, the most frequently involved locations of non-enhancing T2-FLAIR hyperintensity lesions were deep and juxtacortical white matter.…”
Section: Discussionsupporting
confidence: 55%
“…It has been observed that the non-enhancing T2-FLAIR hyperintensity lesions at a distance from the enhancing tumor site at baseline have the neoplastic nature [13]. However, the incidence, location, and shape of these non-enhancing T2-FLAIR hyperintensity lesions in PCNSL are still poorly characterized.…”
Section: Introductionsmentioning
confidence: 99%
“…An impressive example of such a T2-FLAIR lesion and its shrinkage under therapy is depicted in Figure 2 of this paper. 5 Now, of those 16 patients 10 relapsed, five among those showing relapse within the non-enhancing (tumorous) shrinking lesions under therapy. This is in contrast to our usual perception of this disease.…”
Section: See the Article By Tabouret Et Al Pp 422-429mentioning
confidence: 97%
“…10 For practical reasons, however, such an extension of response criteria to these T2-FLAIR lesions seems unnecessary since no case with only nonenhancing relapse has been identified in the series by Tabouret and coworkers. 5 Nevertheless, their observation is of clinical relevance, and we should closely monitor suspicious foci of nonenhancing lesions that increase in size at regular MRI follow-up, particular;y if those lesions had shown shrinkage under first-line therapy.…”
Section: See the Article By Tabouret Et Al Pp 422-429mentioning
confidence: 99%